Pengaruh Tekanan, Kesempatan, Rasionalisasi, Kemampuan, dan Arogansi terhadap Perilaku Kecurangan Akademik Mahasiswa Pendidikan Ekonomi - Solihat, Waffa Mardiatus; Hermawan, Yoni; Nurdianti, Raden Roro Suci (Global Education Journal, 2023)
The problem in this study is that students often engage in academic cheating behaviors while pursuing their studies in college. This research is conducted to determine the influence of pressure, opportunity, rationalization, capability, and arrogance on academic cheating behavior among students majoring in Economics Education from the 2020, 2021, and 2022 cohorts, both partially and simultaneously. This study utilizes a quantitative method in the form of a survey with an explanatory survey design. The population of this study consists of all students from the Faculty of Teacher Tarining and Education, from the 2020, 2021, and 2022 cohorts. The sampling technique used is Probability Sampling with the Proportionate Startified Sampling method, which resulted in sample size of 188 students. Data collection is done through questionnaires, and data analysis is conducted using the SPSS 26.0 for Windows software. The research findings are as follows: 1) There is significant influence of pressure on academic cheating behavior with a significance value of 0,046. 2) There is a significant influence of opportunity on academic cheating behavior with a significance value of 0,001. 3) There is a significant influence of rationalization on academic cheating behavior with a significance value of 0,000. 4) There is a significant influence of capability on academic cheating behavior with a significance value of 0,000. 5) There is a significant influence of arrogance on academic cheating behavior with a significance value of 0,030.